Analyzing the influence of urban mobility on transport-related carbon dioxide emissions in Cagayan De Oro City, Philippines - Dalde, Maricel Cultura; Vilas Nitivattananon; Sharma, Deepak; Sarawut Ninsawat; University of Science and Technology of Southern Philippines {u2013} Cagayan de Oro (USTP-CDO); AIT Scholarship (Pathum Thani : Asian Institute of Technology, 2025)
Transport-related COb2 (Bemissions are a major contributor to climate change, with urban areas playing a crucial role in both their generation and mitigation. The continued rise in these emissions is primarily driven by increasing demand for urban mobility, resulting from continuous population growth and urban expansion. As cities become more populated, the demand for land increases, directing to the outward spread of urban areas. This expansion often increases travel distances and fosters greater reliance on private vehicles, particularly in areas where public transportation infrastructure is limited or underdeveloped. Consequently, these patterns contribute to higher levels of fuel consumption and transport-related COb2 (Bemissions. Thus, it is essential to understand the interactions between urban mobility and transport-related COb2 (Bemissions to effectively mitigate climate change. This study employed an empirical approach to examine the influence of urban mobility on transport-related COb2 (Bemissions. First, an origin and destination survey were conducted to gather data the respondents{u2019} the socio-economic information, their travel behavior, and individual transport-related COb2 (Bemissions. Second, the relationship between travel behavior and emissions was analyzed using multiple linear regression. Third, spatial analysis techniques were applied to examine the urban form characteristics. Fourth, the effects of urban form and socio-economic aspects on COb2 (Bemissions, with travel behavior acting as a mediating factor, were investigated using structural equation modeling. Based on the results, a list of mitigation strategies to reduce transport-related COb2 (Bemissions was developed. Finally, these strategies were evaluated by experts through multi-criteria decision analysis (MCDA) to determine the most effective measures for promoting sustainable urban mobility. The findings indicate that longer travel distances, frequent trips, private vehicle usage, and household income are key contributors to transport-related COb2 (Bemissions. In contrast, increased reliance on public transportation and electric vehicles is linked to lower emissions. While urban form directly impacts emissions, its indirect effect through travel behavior is minimal. Socio-economic factors do not directly affect emissions but significantly influence travel behavior, which in turn contributes to emissions. Mitigation strategies include modernizing public transit, enhancing non motorized infrastructure, implementing green, land-use mix and transit-oriented development strategies, and adopting online services to reduce travel distances, trip frequency, and car dependence. This research enhances the broader knowledge of sustainable urban mobility by highlighting that reducing transport-related COb2 (Bemissions is not merely a technical challenge, but a complex issue influenced by socio economic factors, travel behavior, and urban form. It underscores the necessity of an integrated approach that combines urban planning, transport policy, socio-economic interventions, and behavioral incentives to effectively mitigate COb2 (Bemissions. s
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Urban Innovation and Sustainability
Thesis (Ph.D.) - Asian Institute of Technology, 2025
Keywords: Urban transportation -- Phillippines; Transportation -- Energy consumption -- Phillippines; Carbon dioxide mitigation